Analisis Karakteristik Lokasi Warung Kopi di Kota Makassar - Ahmad Asyraf Thufail; Ihsan Ihsan; Laode Muh. Asfan Mujahid (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2022)
Along with the increase in population in Makassar City, increasing business profitability, the development of product sales was also optimized. The more competition between coffee shops resulted in the Coffee Shop gradually experiencing a decrease in business profitability indicated by a decrease in the number of visitors, for that the author will conduct research on coffee shops in Makassar City related to the characteristics of each coffee shop in Makassar City in knowing regional carriers against each coffee shop in Makassar City. The analytical method used is descriptive qualitative and quantitative analysis, spatial analysis, and scoring analysis. Data collection methods used were field survey interviews, distributing questionnaires, documentation and literature review. This research lasted for seven months from November 2020 to May 2021. The results of the analysis show that the distribution of coffee shops and cafes can be seen in the distribution of coffee points in each sub-district in Makassar City where there are 628 coffee shop data with residential zones which are areas that are always located at every point of coffee shops and cafes.